Development of a scenario-based stormwater management planning support system for reducing combined sewer overflows (CSOs). (15th April 2019) - Fu, Xin; Goddard, Haynes; Wang, Xinhao; Hopton, Matthew E.
Abstract: Using combined sewer systems to handle excess stormwater runoff is common in older urban areas. Combined sewer overflow (CSO) events occur when hydraulic capacity is exceeded, and untreated wastewater discharges to surface waters. As urban population density increases, and more demand is placed on infrastructure, CSO events happen more often and cause serious environmental problems and public-health risks. Recently, green infrastructure (GI) has been integrated with existing gray infrastructure (GrayI) to reduce CSO events. However, there lacks a goal-oriented planning framework for eliminating CSOs at a watershed/sewershed scale. Moreover, existing stormwater simulations based on catchments or other geographic units, do not consider spatial variation within the unit, such as distribution, attribution, ownership, and management of GI. We propose a scenario-based Stormwater Management Planning Support System for CSOs (SMPSS-CSO) to provide a platform for reducing CSO events by coordinating parcel-based installations of GI. We applied the SMPSS-CSO to a sewershed with a single CSO location in Cincinnati, Ohio and developed four scenarios representing increased use of GI (rain barrels, green roofs, porous pavements, and detention basin) based on its cost, difficulty of installation, and property ownership. Runoff quantity, time of concentration, and peak flow rate were simulated using the curve number method. Our analysis shows a 41% reduction in stormwater runoff is necessary to eliminate CSO events for a two-year rainfall, required 97.25% of private and 27.59% of public parcels to install GI. GI alone cannot eliminate CSO events in this sewershed and must be incorporated with additional GrayI (e.g., storage tanks, pipes). The SMPSS-CSO has the potential for including multiple stakeholders' preferences and concerns in the searching for preferable scenarios. Highlights: Proposed a scenario-based planning support system to provide a platform for reducing CSO events. Developed scenarios of parcel-based GI installations (rain barrels, green roofs, porous pavements, and detention basin). Suggested the combination using of GI and gray infrastructure to eliminate CSO events for a two-year rainfall. Discussed applicability of SMPSS-CSO to include stakeholders' preferences and concerns in searching preferable scenarios.